2012
DOI: 10.1519/jsc.0b013e31824f233e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weightlifting vs. Kettlebell Training on Vertical Jump, Strength, and Body Composition

Abstract: Effects of weightlifting vs. kettlebell training on vertical jump, strength, and body composition. J Strength Cond Res 26(5): 1199-1202, 2012-The present study compared the effects of 6 weeks of weightlifting plus traditional heavy resistance training exercises vs. kettlebell training on strength, power, and anthropometric measures. Thirty healthy men were randomly assigned to 1 of 2 groups: (a) weightlifting (n = 13; mean ± SD: age, 22.92 ± 1.98 years; body mass, 80.57 ± 12.99 kg; height, 174.56 ± 5.80 cm) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 3 publications
2
67
1
6
Order By: Relevance
“…Since no previous study has investigated the endocrine response to kettlebell exercise, direct comparisons to prior research on the response to exercise mode is not possible. Kettlebell training has been shown to produce neuromuscular training adaptations similar, though lower in magnitude, to those found with traditional resistance training (Manocchia et al, in press;Otto et al, 2012); thus, we will make comparisons between the findings of the present study and the acute endocrine responses to resistance exercise.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Since no previous study has investigated the endocrine response to kettlebell exercise, direct comparisons to prior research on the response to exercise mode is not possible. Kettlebell training has been shown to produce neuromuscular training adaptations similar, though lower in magnitude, to those found with traditional resistance training (Manocchia et al, in press;Otto et al, 2012); thus, we will make comparisons between the findings of the present study and the acute endocrine responses to resistance exercise.…”
Section: Discussionmentioning
confidence: 71%
“…Only a few studies have investigated the efficacy of kettlebell training. Based on these studies, it appears that kettlebell training can improve maximal and explosive strength (Lake & Lauder, 2012), performance in Olympic weightlifting and powerlifting (Manocchia, Spierer, Lufkin, Minichiello, & Castro, in press;Otto, Coburn, Brown, & Spiering, 2012), and aerobic capacity (Farrar, Mayhew, & Koch, 2010;Hulsey, Soto, Koch, & Mayhew, 2012); thus, kettlebell training may provide an efficient method for simultaneous endurance and resistance training.…”
Section: Introductionmentioning
confidence: 99%
“…The startup and pitch movements are greatly responsible for the lower limbs muscle development (Channell & Barfield, 2008;Arabatzi & Kellis, 2012), mainly of the quadriceps, hamstrings and gluteus maximus (DeWeese et al, 2012). Other studies had already shown that the muscular demand required during the weightlifting practice results in a great increase of strength of lower limbs, and, consequently, of the PT when compared to other training methods from different fields of sport (Tricoli et al, 2005;Khamoui et al, 2011;Otto et al, 2012). Nevertheless, when compared to other fields of sport, the best results of weightlifters were at slow speed (60º/s).…”
Section: Juliete Palandi Elizze Ziero Ducatti Michele Poletti Vinímentioning
confidence: 97%
“…In addition to the work by Lake et al [7], other studies have shown the efficacy of kettlebell training in improving strength and power. Otto et al [9] found that kettlebell training improved improves muscular strength and power but not to the extent that traditional resistance training does. In this study 31 subjects were assigned to either a kettlebell training protocol or a resistance training protocol, which acted as the control.…”
Section: /3mentioning
confidence: 99%